Delaying ACL reconstruction and treating with exercise therapy alone may alter prognostic factors for 5-year outcome: an exploratory analysis of the KANON trial - Filbay, S; Roos, E; Frobell, R; Roemer, F; Ranstam, J; Lohmander, L (BMJ Publishing Group, 2017)
Aims Identify injury-related, patient-reported and treatment-related prognostic factors for 5-year outcomes in acutely ACL-ruptured individuals managed with early reconstruction plus exercise therapy, exercise therapy plus delayed reconstruction or exercise therapy alone. Methods Exploratory analysis of the Knee Anterior Cruciate Ligament, Nonsurgical versus Surgical Treatment (KANON) trial (ISRCTN84752559). Relationships between prognostic factors (baseline cartilage, meniscus and osteochondral damage, baseline extension deficit, baseline patient-reported outcomes, number of rehabilitation visits, graft/contralateral ACL rupture, non-ACL surgery and ACL treatment strategy) and 5-year Knee Injury and Osteoarthritis Outcome Score (KOOS) pain, symptoms, sport/recreation and quality of life (QOL) scores were explored using multivariable linear regression. Estimates were adjusted for sex, age, body mass index, preinjury activity level, education and smoking. Results For all participants (n=118), graft/contralateral ACL rupture, non-ACL surgery and worse baseline 36-item Short-Form Mental Component Scores were associated with worse outcomes. Treatment with exercise therapy alone was a prognostic factor for less knee symptoms compared with early reconstruction plus exercise therapy (regression coefficient 10.1, 95% CI 2.3 to 17.9). Baseline meniscus lesion was associated with worse sport/recreation function (−14.4, 95% CI −27.6 to –1.3) and osteochondral lesions were associated with worse QOL (−12.3, 95% CI −24.3 to –0.4) following early reconstruction plus exercise therapy. In the same group, undergoing additional non-ACL surgery and worse baseline KOOS scores were prognostic for worse outcome on all KOOS subscales. Following delayed reconstruction, baseline meniscus damage was a prognostic factor for less pain (14.3, 95% CI 0.7 to 27.9). Following exercise therapy alone, undergoing non- ACL surgery was prognostic for worse pain. Conclusions Treatment-dependent differences in prognostic factors for 5-year outcomes may support individualised treatment after acute ACL rupture in young active individuals.